Risk Management Dalam Meningkatkan Profitabilitas Di BMT Tanjung - Lailatus Saadah; Moh. Saiful Syuib, M.E (IAIN Langsa, 2022)
Risk management in increasing profitability at BMT Tanjung. This research is based on the effectiveness of risk management to increase the profitability of BMT Tanjung in 2 periods. The number of risks in service products certainly makes BMT Tanjung have a risk management strategy that does not have a bad impact on profits. The purpose of this research is to find out how the risk management strategy of Tanjung BMT and whether it is efficient or not in increasing profitability. The research method used descriptive qualitative methods, data collection techniques conducted interviews, observations, and documentation. The research analysis used descriptive qualitative analysis. Based on the research results, BMT Tanjung's risk management strategy starts from applying for financing, evaluating the 5C of financing, conducting a survey to the customer's residence, if there is a non-performing loan, the customer will be given a choice according to the contract. It can be concluded that after the financial statement data of Tanjung BMT was examined using the profitability ratios of GPM, NPM, ROA, and ROE, it was found that the risk management strategy of Tanjung BMT was considered effective in increasing profitability.